2005
DOI: 10.1897/04-604r.1
|View full text |Cite
|
Sign up to set email alerts
|

The Prestige oil spill. I. Biodegradation of a heavy fuel oil under simulated conditions

Abstract: In vitro biodegradation of the Prestige heavy fuel oil has been carried out using two microbial consortia obtained by enrichment in different substrates to simulate its environmental fate and potential utility for bioremediation. Different conditions, such as incubation time (i.e., 20 or 40 d), oil weathering, and addition of an oleophilic fertilizer (S200), were evaluated. Weathering slowed down the degradation of the fuel oil, probably because of the loss of lower and more labile components, but the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 49 publications
6
52
3
Order By: Relevance
“…The aliphatic fraction from abiotic controls ( Fig. 2A), which was similar to that of the initial fuel added to the cultures, exhibited a bimodal distribution of the n-alkanes, centered at n-C 16 and n-C 26 and extending up to n-C 40 , which is typical of a heavy petroleum residue diluted with a middle-distillate product (10). This profile revealed a slight degree of weathering with respect to fuel recovered directly from the tanker, for example, the pristane/phytane ratio was 0.62 instead of the 0.98 of the original Prestige fuel oil.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The aliphatic fraction from abiotic controls ( Fig. 2A), which was similar to that of the initial fuel added to the cultures, exhibited a bimodal distribution of the n-alkanes, centered at n-C 16 and n-C 26 and extending up to n-C 40 , which is typical of a heavy petroleum residue diluted with a middle-distillate product (10). This profile revealed a slight degree of weathering with respect to fuel recovered directly from the tanker, for example, the pristane/phytane ratio was 0.62 instead of the 0.98 of the original Prestige fuel oil.…”
Section: Resultsmentioning
confidence: 80%
“…For example, given the resistance of 9-methyl phenanthrene to microbial oxidation in relation to the other isomers, the ratio of 3-methylphenanthrene plus 2-methylphenanthrene to 9-methylphenanthrene plus 1-methylphenanthrene has been utilized as a diagnostic ratio (47). These ratios have been defined on the basis of analysis of environmental samples (47) and results of crude oil biodegradation assays with mixed cultures (10,48) or single strains (2,41), mainly alkane-degrading pseudomonads. The actions of high-molecular-weight-PAH-degrading mycobacteria on the alkylated families of PAHs present in crude oil and derivatives have not been addressed.…”
mentioning
confidence: 99%
“…Because the Prestige oil was composed of both alkanes and aromatic hydrocarbons, the stimulation of a specific degrader population suggests that the alkane-degrading community responded more rapidly in these sediments; this conclusion was supported by a low nC18/phytane ratio (see Fig. S1b in the supplemental material) (56). Still, the presence of bssA-like sequences in the untreated sample suggests a low basal level of hydrocarbons in this area (e.g., through sporadic bilge water discharges), which would sustain such microbial populations.…”
Section: Resultsmentioning
confidence: 86%
“…1), oil-polluted samples were taken from the supralittoral zone of a cobblestone beach located next to Faro Lariño (42°46Ј25ЉN, 09°07Ј30ЉW, The extent of biodegradation of each compound was measured from the normalized peak area of the target analyte referred to that obtained from the same compound in the control sample (2,28). The peak areas of the target analytes were measured in the reconstructed ion chromatograms at m/z 85 for aliphatics and at the corresponding molecular ion for the aromatics as described elsewhere (16).…”
Section: Samplingmentioning
confidence: 99%
“…Culture-independent and -dependent analyses showed that Actinobacteria, mainly Rhodococcus species, was the key alkane-degrading group of bacteria. Rhodococcus has been associated with the degradation of n-alkanes up to C 36 (65) and branched alkanes (64), which are particularly abundant in the Prestige fuel (16). It is well known that Rhodococcus is a genus with remarkable metabolic diversity (36) and is able to produce biosurfactants which can enhance not only the bioavailability of fuel components but also the growth of other degrading bacteria (26,47).…”
mentioning
confidence: 99%